Advances in In Situ TEM for Dynamic Studies of Carbon-Based Anodes in Alkali Metal-Ion Batteries - Cui, Jinchao; Zhang, Jiyun; Jing, Jingyi; Wang, Ya; Du, Gaohui; Yang, Yongzhen; Yan, Lingpeng; Su, Qingmei (Advanced Functional Materials, 2024)
High-energy-density anode materials are crucial for achieving high performance alkali metal-ion batteries (AMIBs). In situ transmission electron microscopy (TEM) enables real-time observation of microstructural changes in electrode materials and interfaces during charging/discharging, crucial for designing high-performance anodes. This paper highlights and reviews the dynamic studies of the relationship between the structure and the electrochemical performance of carbon-based composite materials used as anodes in AMIBs by in situ TEM. First, the in situ TEM technique and cell construction method are introduced, followed by an overview of in situ TEM integrates with other advanced measurement techniques. Second, the fundamental working principles of various AMIBs and the energy storage mechanisms of anode materials are explained, along with the achievable functions of in situ TEM in AMIBs. Third, from different carbon matrix structures, including carbon-supported, carbon-embedded, carbon-coated, carbon-encapsulated, and hybrid carbon-composite structures, in situ dynamic studies on the electrochemical behaviors of these carbon-based anode materials by TEM are covered in depth. Finally, a summary of the design ideas and the technical application of in situ TEM for carbon-based anode composites is provided, followed by a suggestion for current challenges and future research paths.
CRIS-Team Scopus Importer:2024-12-06
Keywords: alkali metal-ion batteries (AMIBs); anode materials; carbon-based composites; electrochemical performance; in situ transmission electron microscopy (TEM)